Evaluation of Some Agricultural and Industrial Wastes as a Compost for the Cultivation of Pleurotus spp. - Akyuz, Mehmet; Kirbag, Sevda (Foundation Environmental Protection & Research-Fepr, 2009)
This research was to study the possibility of using local agricultural and industrial wastes for the cultivation of Pleurotus species. For the propagation of the main culture 2% malt extract agar was used whereas wheat grains were used for the propagation of spawn. For the formation of basidiocarp, wheat straw (WS), cotton straw (CS), corn straw (AS), rice brau (BS), lentil straw (AS), bean straw (BS), soybean straw (SS) and pelt waste (PW) were used as culture media. The shortest mycelium growing period was determined as average 10 days on WS-BS (1:1) + 5% RB for P. eryngii the longest was 15 days on WS-CS (1:1) + 5% RB for P. eryngii var. ferulae. The shortest primordium formation period was determined as 28 days on WS-SS (1:1) + 5% RB for P. ostreatus, while the longest was 103 days on WS-CS (1:1) + 5% RB for P. eryngii var. ferulae The harvest period was determined as 33 days oil WS-AS (1:1) + 5% LS for P sajor-caju, while the longest was 116 days on WS-CS (1:1) + 5% RB for P. eryngii var. ferulae. The lowest average yield per 100 g of material (70% moisture) was 15 g on WS + 5% PW for P. eryngii, while the highestwas 22 g on WS-BS (1:1) + 5% RB for P. eryngii. In conclusion, it was determined that various local agricultural and industrial wastes call be used for the cultivation of Pleurotus spp.
Bazı tarımsal ve endüstriyel atıkların Pleurotus spp. Üretiminde kompost olarak de?erlendirilmesi
Keywords: Agricultural wastes; mushroom cultivation; pelt waste; Pleurotus spp.